2016
DOI: 10.1002/eat.22497
|View full text |Cite
|
Sign up to set email alerts
|

Increased use of antimicrobial medication in bulimia nervosa and binge‐eating disorder prior to the eating disorder treatment

Abstract: Indicating increased infections, we found elevated use of antimicrobial medication in BN, BED and in males with AN. Infections may be consequence of hyperglycemia, weight gain, or dysregulation of intestinal microbiota associated with core eating disorder behaviors. Or the other way round; changes in intestinal microbiota due to infections, inflammation, or antibacterial medications might contribute to eating disorders in multiple ways. © 2016 Wiley Periodicals, Inc. (Int J Eat Disord 2016; 49:542-552).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 44 publications
4
13
0
Order By: Relevance
“…Reports also show that dementia is related to peripheral pro-inflammatory factors released by periodontal inflammatory mediators such as C-reactive protein, IL-6, haptoglobin, TNF-α, and fibrinogen ( 76 – 78 ). Furthermore, some studies have also found that inflammation play an important role in eating disorders ( 79 , 80 ) and sleep disorders ( 81 83 ).…”
Section: Discussionmentioning
confidence: 99%
“…Reports also show that dementia is related to peripheral pro-inflammatory factors released by periodontal inflammatory mediators such as C-reactive protein, IL-6, haptoglobin, TNF-α, and fibrinogen ( 76 – 78 ). Furthermore, some studies have also found that inflammation play an important role in eating disorders ( 79 , 80 ) and sleep disorders ( 81 83 ).…”
Section: Discussionmentioning
confidence: 99%
“…Escherichia coli K12 and Body Mass Index (Million et al, 2013). Bulimia nervosa (BN) and binge-eating disorder (BED) diagnoses on the other hand have been correlated to antimicrobial medication use prior to ED treatment (Raevuori et al, 2016).…”
Section: Gut Microbiota Dysbiosis and Edsmentioning
confidence: 99%
“…Several studies suggest that both obesity and underweight can increase the risk of viral infection in a Ushaped manner, which holds in particular for influenzarelated pneumonia [1]. Paradoxically, despite serious malnourishment and alterations in immune functions, it has been reported that anorexia nervosa (AN) seems to be associated with fewer symptomatic viral infections [2][3][4]. However, because of the paucity, contradictions and methodological shortcomings of previous studies [2][3][4][5], extreme care must be taken in drawing any firm conclusion.…”
Section: The Risk Of Covid-19 Infection In Patients With Ed -Safety Recommendationsmentioning
confidence: 99%